2004
DOI: 10.1002/jbm.b.30127
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of orthopedic composite cytotoxicity: Assessing the potential for postsurgical production of hydroxyl radicals

Abstract: Hydroxyl radical (⅐OH)-induced inflammation is a primary mode for in vivo cytotoxicity. A legitimate concern is whether particulate wear debris from orthopedic composites can stimulate inflammation via ferrous ion (Fe 2؉ )-mediated production of ⅐OH. The purpose of this research was to utilize electron paramagnetic resonance (EPR) spin trapping in investigating and comparing the potential for postsurgical cytotoxicity induced specifically by ⅐OH in the presence of two composites: Simplex P and the novel, hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, Cortoss was found to be like a free radical scavenger, an important feature of this material. 24 We have to underline that bis-GMA-based allograft may not be suitable in cases of very large bone defects. Glass ionomer cement proposed by Helms and Geyer 11 was stated to be available for shaping outside the body before application and hardening, thus allowing to obtain a material to fit exactly to a large bone defect.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, Cortoss was found to be like a free radical scavenger, an important feature of this material. 24 We have to underline that bis-GMA-based allograft may not be suitable in cases of very large bone defects. Glass ionomer cement proposed by Helms and Geyer 11 was stated to be available for shaping outside the body before application and hardening, thus allowing to obtain a material to fit exactly to a large bone defect.…”
Section: Discussionmentioning
confidence: 98%
“…They combined a biodegradable polymer (PHB or PHBV) with bioactive glass filler as silicate-based glass or borate-based glass. [42,49,50] Pure PMMA cement and those containing PHB and PHBV, were assayed for cell viability/proliferation (MTT assay) in cells of human bone marrow, under conditions that promoted osteoblastic differentiation, 62 for twenty one days. Results are shown in Figure 2, they indicated that PHBV containing cements had improved performance.…”
Section: Bioactive Bone Cementsmentioning
confidence: 99%
“…Cortoss Ò has osteoconductive properties [139], but is not resorbed [140]. It does not induce cytotoxicity [141], and offers biocompatibility and reduced risk of thermal necrosis [142].…”
Section: Biological Propertiesmentioning
confidence: 99%